2018
DOI: 10.3892/ijmm.2018.3900
|View full text |Cite
|
Sign up to set email alerts
|

eRF3b-37 inhibits the TGF-β1-induced activation of hepatic stellate cells by regulating cell proliferation, G0/G1 arrest, apoptosis and migration

Abstract: The therapeutic management of liver fibrosis remains an unresolved clinical problem. The activation of hepatic stellate cells (HScs) serves a pivotal role in the formation of liver fibrosis. In our previous study, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALdI-TOF MS) was employed to identify potential serum markers for liver cirrhosis, such as eukaryotic peptide chain releasing factor 3b polypeptide (eRF3b-37), which was initially confirmed by our group to serve a protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A well-known fact is that activated HSCs are the main source of stroma-secreting myofibroblasts that cause liver fibrosis [29]. In an activated state, the proliferation capacity of HSCs is promoted, and apoptosis is reduced [30]. Our results showed that SS-31 could block the proliferation of TGF-β1-activated LX2 cells and promote cell apoptosis, suggesting that SS-31 could effec-tively block HSC activation.…”
Section: Discussionmentioning
confidence: 60%
“…A well-known fact is that activated HSCs are the main source of stroma-secreting myofibroblasts that cause liver fibrosis [29]. In an activated state, the proliferation capacity of HSCs is promoted, and apoptosis is reduced [30]. Our results showed that SS-31 could block the proliferation of TGF-β1-activated LX2 cells and promote cell apoptosis, suggesting that SS-31 could effec-tively block HSC activation.…”
Section: Discussionmentioning
confidence: 60%
“…As we all know, activated HSCs are the major cellular source of matrix protein-secreting myofibroblasts which are the major driver of liver fibrogenesis [ 5 ]. When TGF- β 1 induced HSCs activation, the proliferation and migration ability were significantly upregulated, and cell apoptosis was decreased [ 35 ]. Our results showed that FA at a safe dose could significantly inhibit the proliferation and migration of LX2 cells induced by TGF- β 1, indicating that FA could effectively inhibit the activation of HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It proves to promote the differentiation of fibroblasts into α‐SMA‐positive myofibroblasts and myofibroblasts proliferation by mediating different signaling pathways, including canonical Smad2/3 pathway and noncanonical pathways . In addition, several researchers pointed out that TGF‐β1 could regulate cell cycle and promote cell proliferation . Herein, TGF‐β1 appears to play an important role in the development of tendon fibrosis.…”
Section: Introductionmentioning
confidence: 99%